Pengaruh Big-Five Personality Dan Environmental Justice Terhadap Citizenship Behavior Toward Environment Peserta Didik di SMAN Jakarta - Siahaan, Hossiana Ekklesia (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
Global warming in Indonesia is caused by the increase in GHG from landfills. Character education is expected to form citizenship behavior towards the environment in students. This research aims to determine the effect of big-five personality and environmental justice on citizenship behavior toward environment. The method used is a survey method through causal studies and analyzed using path analysis. This research was conducted toward 80 students at SMAN Jakarta in odd semesters of the 2022/2023 academic year. The result of reliability coefficient of citizenship behavior towards environment was 0.898, big-five personality was 0.923, and environmental justice was 0.872. The result show that big-five personality has a direct effect on citizenship behavior toward environment,environmental justice has a direct effect on citizenship behavior toward environment, big-five personality has a direct effect on environmental justice, and environmental justice is not a good mediator between big-five personality and citizenship behavior toward environment.